Efficacy of vancomycin in combination with various antimicrobial agents against clinical methicillin resistant Staphylococcus aureus strains - Aktas, Gulseren (Pak J Med Sci, 2021)
BACKGROUND: Multi-drug resistant methicillin resistant Staphylococcus aureus (MRSA) strains that have been isolated frequently worldwide have difficulties in the treatment and therefore alternative choices for the treatment of the infections are required. The aim of the study was to evaluate the interaction of various antimicrobials in combination with vancomycin against MRSA. METHODS: Twenty five clinical MRSA strains isolated in 2016 were included in the study. The interaction between vancomycin and new generation/conventional antimicrobials against MRSA strains was analyzed by E-test. RESULTS: All of the strains tested was found to be susceptible to vancomycin, telavancin, dalbavancin, ceptobiprole, daptomycin, linezolid, quinupristin-dalfopristin, trimethoprim-sulfamethoxazole, rifampicin and tigecycline. The susceptibility rates of the isolates were found to be high, with the lowest rate (48%) against azithromycin. According to the fractional inhibitory concentration index results, synergistic interaction with vancomycin was determined with trimethoprim-sulfamethoxazole, azithromycin, linezolid, minocycline, dalbavancin, clindamycin in five, three, two, two, one, one and one strain(s), respectively. Additionally, all combinations studied showed additive interaction at high rates. CONCLUSIONS: The results of the study indicate that the use of vancomycin in combination with conventional and new generation antibiotics is promising.